Comparação entre três protocolos para o retorno ao esporte durante a pandemia de COVID-19 - Moura, J. E. N.; Feitosa, I. D. A. F.; Nogueira, G. M. C.; de Oliveira Villarim, P. V.; Teixeira, T. A. L.; de Lima, J. G. (Revista De Medicina, 2021)
Introduction: As the COVID-19 spread across the world, many activities had to adapt to the new challenging scenario, involving new safety measures such as strategies of social isolation. Since professional sports have a considerable potential of causing agglomerations, they also had their competitions suspended or postponed. However, as the situation lasted longer than previously expected, there was a necessity to get these tournaments resumed with adaptations. So that could happen safely and in agreement with the current moment, the creation of effective protocols and in harmony with the medical guidelines became essential. Objective: To compare the protocols published by the institutions of some professional sports events and leagues and to point possible contributions that can be given by the medicine, especially sports medicine at a COVID-19 pandemic scenario. Methods: This is a narrative review made in two research phases: in databases (PubMed, ScienceDirect and Scielo) and in official sites and wide visibility daily journals. The data were collected during 2020 August. The Union of European Football Associations (UEFA), National Basketball Association (NBA) and Confederação Brasileira de Futebol (CBF) protocols were selected. Results: Different strategies established by the institutions against COVID-19s dissemination were found. UEFA and NBA converged with the strict rules` definition for the players and staff members isolation, virus testing guidelines and teams transfer between games. These resources, however, were not present in CBF`s politics, since the organization did not follow the same rigidity. The organizations, nevertheless, had one common proposition: the crowd suspension during the games. Besides that, in both protocols, the athletes` physical integrity issue was not approached. Conclusion: The organizations` measures focused on control of the virus transmission and the safety of all involved during COVID-19`s pandemic, that demonstrates a cooperative work and a close medical participation with the sports community. Either way, a better clinical perspective in muscular health and athletes` immunity was demonstrated necessary.